The Heyman Survey of nursing employees' attitudes towards mechanical restraints in Slovenia - Bregar, Branko (Obzornik zdravstvene nege, 2019)
Introduction: Attitudes of nursing employees towards mechanical restraint are directly connected to their incidence. The purpose of this research was to examine the attitudes of psychiatric nursing staff towards the use and administration of mechanical restraints. Methods: The cross-sectional descriptive study was conducted using a structured Heyman-type survey. All the Slovenian nursing staff in psychiatric hospitals participated on a given day (n = 367). Results: Differences were observed in the average duration of administered mechanical restraint between individual hospitals (x2 = 43.770, p < 0.001). Staff most often stated that patients felt angry when subjected to mechanical restraint (n = 328, 89.4 %). Nonetheless, the majority of respondents believe that mechanical restraints can be an effective therapeutic tool (n = 343, 91.6 %). Females (U = 11450.50, p = 0.025) and with higher education (U = 9527.00, p = 0.002) experience statistically significantly more negative emotions and are less inclined to use mechanical restraints. Discussion and conclusion: It is evident that in addition to the factors we researched some other factors are more influential when the incidences of coercive measures are closely studied. Due to some variation between hospitals it would be advisable to review the current clinical practices in this field. The management of health institutions should be considered an essential factor in the efforts to decrease mechanical restraint use.
Keywords: coercive measures; medicinske sestre; nasilje; nurses; nursing; prisilni ukrepi; psihiatrija; psychiatry; violence; zdravstvena nega